1993
DOI: 10.1111/j.1399-3038.1993.tb00087.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical properties of aeroallergens: contributory factors in allergic sensitization?

Abstract: Recent studies indicate that the majority of clinically important aeroallergens are biochemically active. A diverse range of properties have been demonstrated but most possess either enzymatic activity (principally hydrolytic), enzyme inhibitory activity, low molecular weight ligand transporting or regulatory properties. In addition, some allergens are glycosylated and/or are structurally similar to proteins which have evolved to function in the respiratory system per se. Little attention has been given to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 91 publications
0
18
0
Order By: Relevance
“…There is evidence that at least proteases have, in addition to their allergenic potency, direct effects on epithelial integrity and permeability, mast cell degranulation, cytokine release from the respiratory epithelium and, further, exhibit interactions which may influence the pathogenesis of allergic and non-allergic airway disorders (Stewart et al 1993). Recent studies show that proteases can react with cell surface receptors (proteaseactivated receptors) in the airways.…”
Section: Amplification Of Allergies and Direct Induction Of Inflammatmentioning
confidence: 98%
“…There is evidence that at least proteases have, in addition to their allergenic potency, direct effects on epithelial integrity and permeability, mast cell degranulation, cytokine release from the respiratory epithelium and, further, exhibit interactions which may influence the pathogenesis of allergic and non-allergic airway disorders (Stewart et al 1993). Recent studies show that proteases can react with cell surface receptors (proteaseactivated receptors) in the airways.…”
Section: Amplification Of Allergies and Direct Induction Of Inflammatmentioning
confidence: 98%
“…However, progress made in allergen characterization has shown that the majority of clinically important allergens have biochemical functions. Most allergens are enzymes or regulatory proteins [28]. Serine proteinases such as trypsin and chymotrypsin have been identified as the group 3 and the group 6 major allergens of the house dust mite D. pteronyssinus [29, 30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Of particular importance to this study are the carbohydrate-binding receptors such as the C-type lectins or the ␤-glucan receptor. These receptors have specificities for terminal sugar groups rarely found in mammalian systems but which are common constituents of pollen, bacteria, and fungi (22), suggesting the possibility that they play a role in innate recognition of AP such as PSG. The interaction of AP with receptors on AM has the potential to stimulate production of various mediators including NO.…”
Section: T He Respiratory Tract (Rt)mentioning
confidence: 99%